Agricultura y empleo rural agropecuario en Bolivia: Consecuencias del control de precios en el sector agropecuario - Diego Alejandro Vera Cossío (Institute for Advanced Development Studies (INESAD), 2011)
– Price controls are measures that can significantly affect the sectors subject to such policies. Using a dynamic general stochastic equilibrium model with two types of agents: farmers and city dwellers, calibrated to Bolivia, it is shown that with falling productivity in the agricultural sector, agricultural rural employment and agricultural production were impaired when there are price controls. Likewise, productivity improvements in the rural non-farm sector, represents lower incomes with fixed prices in relation to a mechanism that allows prices to adjust. In a simulation of the policies carried out in 2009 in Bolivia, we can see that they create imbalances in the markets causing shortages of agricultural products in substantial quantities.
Keywords: O13; Q11; R13; 330; Price Control; Rural Employment; Agriculture; Beschäftigung; Ländlicher Raum; Agrarpreispolitik; Bolivien